STUDENTS’ PERCEPTION OF COMPUTER-BASED TESTING-EDUBOX– AND ITS IMPACT ON THEIR ENGLISH LEARNING MOTIVATION - Amalia Rahisa Dewi; Andang Saehu; Rahmat Budiman (Universitas Kuningan, 2021)
Learning motivation as a part of learning process needs to be scrutinized by reason of it could trigger the students to achieve their learning performance successfully. There are no specific studies about students’ perception towards Edubox as a kind of computer-based testing (CBT) and its impact to the students’ English learning motivation. This study is intended to examine the relationship between students’ perception about the use of Edubox as an assessment tool with their English learning motivation. Mixed methods are conducted to get more meaningful findings. Data collection is conducted through administering English test using Edubox, observation, questionnaires, and focused group discussion (FGD) as the primary data. Inferential statistics: T-test and Pearson correlation test are used to analyse quantitative data. While, the FGD result are analysed using Spreadly domain analysis method. 253 of 843 total populations are selected as the sample of the study utilizing stratified sampling. They take English test using Edubox, and are given questionnaires as well. Observation is done simultaneously by means of video recorders from smart phones during the English test administration. 30 students are chosen purposively to participate in FGD session. This study found that the majority of participants have negative perception towards the implementation of Edubox as the means to evaluate their performance in English; most specifically due to technical problems they encountered before and during the test. It is represented by the result of correlational test where r-value = 0,550 and t-test p-value is lower than alpha 0,000<0,05. This mean that the relation between students' English score of PBT and that of English score of CBT was significant. Ultimately, it is recommended to conduct preliminary study prior to implementing Edubox in any educational settings and to put extra efforts in minimizing technical factors that have influenced students’ perception towards Edubox negatively. Keywords: Edubox; students’ perception; English learning motivation; English learning performance